Traditional games: a study of Malaysian kites of Wau Bulan in Kelantan / Muhammad Radzuan Mohamed Nihau - Mohamed Nihau, Muhammad Radzuan (2018)
Playing wau or better known as kite were once popular in the interior but now playing wau has begun to be popular by many people including those living in urban areas. This game contains elements of Malay native culture. This can be seen in the form and design of the pattern found on the wau. The research is conducted to study Malaysian Traditional games Wau bulan in Kelantan, which is by making an illustration book about the process of making Wau bulan. By conducting this study, it will enable outsiders to better understand the traditions of Malaysians. This illustration book of the process in making Wau Bulan will help tourists or locals to know the ways and process in producing a perfect Wau bulan and suitable for played. By doing a guidebook or book illustration will make readers better understand, and they will start to create their own Wau bulan with its own design. Perhaps by making their own Wau bulan will make them happier because it's something they've done manually. This Wau Bulan game has its own fiesta and with having this unique fiesta maybe will make tourist and locals more unifying. With having this research it will introduce reader more about a unique Malaysian tradition in Kelantan. Hopefully, this study will show and make the tourist understand more in detail and depth about Wau Bulan Kelantan.